(3GdBdI GdfLhejI JHjf GdChbGJ hGdSGYGJs
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd fhY GdEfSGf Ydi LejY PhGJ Gdchf hGdaSGO ef eYQaI GdejbGJ HBdI eQSheIGdCSWQdGH, dG GdBdI GdeSWMI GdJi CdagG EHQGgje Hf GdRQbd , hGdHWdjehS GdMcje s
(3BNQgG (B:s
(3hYOO GdCPQY GdJi ef bGYOI GdBdI Edi GdfbWI GdeWdhHI ef fbWI GdYeb GdeWdhH hEf CQOJ Cf JYde YOO GdCPQY GdJi eQ fgGjI GdYeb Edi fbWI eG efg Ch ef fbWI eG dfbWI eG JaYd ajg ceG JbOe , jMUd dc GdeWdhH s
(3HgG fXGe GdJYbjHIs
(3bOegG GdeDda Edi GdSdWGf GdYKeGfi HGjRjO Hf eMeO NGf GdeJhai SfI (B1512(3e ChGFd GdbQf GdYGTQ GdgLQis
(3cJHJ Hbde ajg VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs